Penerapan Pembelajaran Berdiferensiasi dalam Pembelajaran Bahasa Indonesia di SMP Negeri 27 Makassar - Hamdiah, Hamdiah; Ramly, Ramly; Idawati, Idawati (Nuances of Indonesian Language, 2025)
This research aims to identify and analyze the implementation of differentiated instruction in the aspects of content, process, and product in Indonesian language learning at SMP Negeri 27 Makassar. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The focus of this research is on the three main aspects of differentiated instruction: content, process, and product. The results show that in the aspect of content, teachers provide varied teaching materials tailored to the interests and needs of students, using diverse sources to enrich the learning experience. In the process aspect, teachers implement various teaching methods, such as collaborative learning and group discussions, to encourage student engagement and enhance their understanding of the material. Meanwhile, in the product aspect, teachers design creative and varied assignments, such as making posters, writing poems, and composing explanatory texts. These tasks are not only aimed at improving students' academic skills but also at developing their creativity, cooperation, and critical thinking abilities. Student product assessments are conducted using a structured rubric, covering criteria such as accuracy, creativity, and communication skills, allowing teachers to provide focused feedback and help students understand the expected outcomes. Through this differentiated approach, teachers have successfully created an inclusive and enjoyable learning environment where every student feels valued and motivated to learn, hypothesis that the inquiry method has a meaningful impact on students' critical and creative thinking abilities. Thus, this research proves that the application of the inquiry method is effective in improving students' abilities in writing explanatory texts, both in terms of quality and variation in critical and creative thinking skills.Â